Efficacy, Safety, and Durability of Voretigene Neparvovec-rzyl in RPE65 Mutation-Associated Inherited Retinal Dystrophy: Results of Phase 1 and 3 Trials - Maguire, Albert M; Russell, Stephen; Wellman, Jennifer A; Chung, Daniel C; Yu, Zi-Fan; Tillman, Amy; Wittes, Janet; Pappas, Julie; Elci, Okan; Marshall, Kathleen A; McCague, Sarah; Reichert, Hannah; et al. (Ophthalmology (Rochester, Minn.), 2019)
To report the durability of voretigene neparvovec-rzyl (VN) adeno-associated viral vector-based gene therapy for RPE65 mutation-associated inherited retinal dystrophy (IRD), including results of a phase 1 follow-on study at year 4 and phase 3 study at year 2. Open-label phase 1 follow-on clinical trial and open-label, randomized, controlled phase 3 clinical trial. Forty subjects who received 1.5×10 vector genomes (vg) of VN per eye in at least 1 eye during the trials, including 11 phase 1 follow-on subjects and 29 phase 3 subjects (20 original intervention [OI] and 9 control/intervention [CI]). Subretinal injection of VN in the second eye of phase 1 follow-on subjects and in both eyes of phase 3 subjects. End points common to the phase 1 and phase 3 studies included change in performance on the Multi-Luminance Mobility Test (MLMT) within the illuminance range evaluated, full-field light sensitivity threshold (FST) testing, and best-corrected visual acuity (BCVA). Safety end points included adverse event reporting, ophthalmic examination, physical examination, and laboratory testing. Mean (standard deviation) MLMT lux score change was 2.4 (1.3) at 4 years compared with 2.6 (1.6) at 1 year after administration in phase 1 follow-on subjects (n = 8), 1.9 (1.1) at 2 years, and 1.9 (1.0) at 1 year post-administration in OI subjects (n = 20), and 2.1 (1.6) at 1 year post-administration in CI subjects (n = 9). All 3 groups maintained an average improvement in FST, reflecting more than a 2 log (cd.s/m ) improvement in light sensitivity at 1 year and subsequent available follow-up visits. The safety profile was consistent with vitrectomy and the subretinal injection procedure, and no deleterious immune responses occurred. After VN gene augmentation therapy, there was a favorable benefit-to-risk profile with similar improvement demonstrated in navigational ability and light sensitivity among 3 groups of subjects with RPE65 mutation-associated IRD, a degenerative disease that progresses to complete blindness. The safety profile is consistent with the administration procedure. These data suggest that this effect, which is nearly maximal by 30 days after VN administration, is durable for 4 years, with observation ongoing.